Standards for evaluating the quality of undergraduate nursing e-learning programme in low- and middle-income countries: a modified Delphi study - Moses Mutua Mulu; Champion N. Nyoni (BMC, 2023)
Abstract Background The lack of standards for evaluating the quality of undergraduate nursing programmes hampers the evaluation of e-learning programmes in low- and middle-income countries. Fragmented approaches to evaluation coupled with a lack of uniform criteria have been a major deterrent to the growth of e-learning. Adopting standards from high-income countries has contextual challenges in low- and middle-income countries (LMICs). Holistic approaches coupled with uniform standards provide information to stakeholders hence the quality of the programmes is measurable. The e-learning situation in low-and middle-income countries provided an impetus to develop and validate these standards. Design A modified Delphi technique. Review methods Fourteen experts with experience and expertise in e-learning and regulation of undergraduate nursing from fourteen countries from LMICs participated in three rounds of the modified Delphi process. A pre-described set of standards was shared electronically for independent and blinded ratings. An 80% threshold was set for consensus decisions. The standards were modified based on experts' comments, and two subsequent rounds were used to refine the standards and criteria. Results At the end of round one, the expert consensus was to keep 67, modify 39 and remove three criteria. At the end of the second round, the consensus was to modify 38 and remove one criteria. In the third round, experts agreed that the standards were feasible, usable, and practical in LMICs. A total of six broad standards with 104 criteria were developed. Conclusion The Technological bloom permeating all spheres of society, including education is an essential component in the development of e-learning programmes. E-learning in nursing education requires critical evaluation to ensure quality in undergraduate nursing programmes. The intricacies of the Low and middle-income context were taken into consideration in developing the standards to offer sustainable evaluation of the quality of e-learning in LMICs, and local solutions to local problems.